Access to investigational medicinal products for minors in Europe: ethical and regulatory issues in negotiating children's access to investigational medicines. Issue 12 (18th September 2010) - Pinxten, Wim; Nys, Herman; Dierickx, Kris
Abstract : Patients who search for a better treatment, an increased quality of life, or even a chance to preserve life itself may claim to have an interest in accessing investigational medicinal products (IMP), particularly when no validated treatment for their disease or condition exists. For many, awaiting the uncertain and time-consuming process of converting an IMP into an approved drug may not appear a realistic option, as prognoses may be grim and a dramatic outcome may seem hard to avert. Gaining access to an IMP, however, often proves to be a difficult enterprise with a highly uncertain outcome. In addition, the process of seeking access to IMP is surrounded by various ethical issues that will be explored in this article. This paper explores the ethical concerns in two potential tracks of seeking access to IMP for minors: on an individual basis, or collectively, as a patient organisation. In this discourse, several unique ethical and regulatory concerns related to the direct negotiation of access to IMP for minor patients are identified, with a focus on product safety, the recruitment of research subjects, the unnoticed entry of market mechanisms in the recruitment of research subjects, and the sidelining of third parties in the recruitment process. The paper concludes with a concise reflection on the way forward. The quest for access to investigational drugs is particularly relevant to paediatric practice, in which a significant share of the drugs prescribed has never been tested in children or labelled for use in the paediatric population.